Kontribusi Dokter Forensik Dalam Pembuktian Perkara Tindak Pidana Di Indonesia - Reinaldy Muhammad; Indra Yudha Koswara (Jurnal Ilmiah Wahana Pendidikan, 2023)
The administration of justice through the judiciary always causes the suspect/defendant to make sacrifices to become the subject of investigation. This is due to the unequal position of the suspect in negotiating with law enforcers, who represent investigators in this case, both from a psychological perspective and their rights and obligations, making it difficult to obtain objective truth. With advances in science and technology, society obtains scientific evidence which is referred to as a silent witness, because it requires the role of experts who research scientific evidence according to their expertise. Physicians, as well as medical staff, are responsible for providing assistance to law enforcement, who are known as forensic specialists. Based on the above background, the identification of the problem in this study is the role of the forensic doctor in proving a criminal case and the role of the forensic laboratory in examining evidence against a crime. The method used in this research is normative juridical research. Methods that can be used to prove a criminal case include asking for help from a doctor as a witness who can make a written statement in the form of a visum et repertum and provide information in court as an expert witness.